PENGEMBANGAN MEDIA PEMBELAJARAN MODUL ELEKTRONIK MATA KULIAH DIAGNOSIS KENDARAAN DI PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNIVERSITAS SRIWIJAYA (Jurnal Pendidikan Teknik Mesin, 2017)
This research is a research & development (R & D). This study aims to produceinstructional media electronics module subjects Diagnosis Vehicle programmed studyMechanical Engineering Education Sriwijaya University in the form of electronic medialearning valid and practical serts have a potential effect, then that would be applied as a mediumof learning both on campus and outside campus. The research location is programmed studyMechanical Engineering Education sriwijaya university in the academic year 2016/2017 in 2014Inderalaya students. Media validity was assessed by two experts, namely, validation matterexperts and media experts. The validity of the material to get 87.96% of the categorized resultsare very valid, the validity sedangan media get 85% were categorized as very valid too. Followedby a one to one interview, in which the comments of the media is very positive, the next to seethe practicality do small group stage, the result is 83.84% of the results included practical. , Inthe field test results received n-gain of 0.90 and in the high category. It can be concluded thatthe electronic module Vehicle Diagnosis is valid, practical, and have a potential effect.